Pengetahuan Perempuan Terhadap Kontrasepsi: Tinjauan Literatur - Yunitasari, Eva; Suri, Susi Irma (Utan Kayu Publishing, 2020)
Program Family Planning , according to WHO (World Health Organization ) in and wife to. avoid births were unwanted , and regulat the distribution of birth,as children in the family. And Many women were difficulties in determining contraception because of ignorance about the requirements and safety contraception is There are several things that can affect some mothers in selecting a tool of contracepion were excluded by level of education, economy, rates of service, approval pasangaan , opinions and knowledge. There are several things that can affect some mothers in selecting a tool of contracepion were excluded by level ofeducation ,economy, rates of service, approval pasangaan , opinions and knowledge. This study aims to examine the results various studies from several journals about maternal knowledge about contraception. The method of research it is Literature Review . the journal used for the literature review last five years 2015-2020. This research was conducted on June 22, 2012 in Gunung Tiga Village, East Lampung Regency. Design studies are taken in search scientific. This is Mixmethos Subjects in this study were post partum mothers. From the study of literature review be in seen in mothers who are knowledgeable, education as well as the mother's attitude then it is rational mother in using the tool of contraception. compared with someonewho studies less then people are going to be difficult to digest and accept the information that he obtained . In a literature review on 10 journal is that discusses about the knowledge of mothers with contraception can not it results that there is a relationship between knowledge, education and attitude and family support to mothers who use contraception. Can develop this research in the family nursing phase in the village by increasing health services in providing counseling or providing information on more effective contraception.